In the Kitchen with Rosie : Oprah's Favorite Recipes - Daley, Rosie (London Ebury, 1994)
When chat show host Oprah Winfrey took on Rosie Daley as cook, her life changed and she started to shed pounds. Here she shares Rosie's low-fat, low-calorie dishes and advocates them to all her fans as part of a balanced, healthy and weight-reducing regime.
Include Index and Illustrations
Keywords: Low-fat diet